2017
DOI: 10.1161/circoutcomes.116.003153
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of Adverse Neurocognitive Outcomes With Proprotein Convertase Subtilisin-Kexin Type 9 Inhibitors

Abstract: Background-There is encouraging evidence of the efficacy of proprotein convertase subtilisin-kexin type 9 (PCSK9) inhibitors; however, their long-term safety remains unclear. We performed a meta-analysis of studies to evaluate the longterm safety of PCSK9 inhibitors. Methods and Results-Our search strategy yielded 11 studies (9 smaller early-phase and 2 larger outcome trials). The outcomes assessed were cumulative serious adverse events, musculoskeletal adverse events, neurocognitive adverse events, and stroke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 39 publications
0
40
0
1
Order By: Relevance
“…De novo glial synthesis of cholesterol in the brain is postulated to be important for synapse formation and function; observational studies and RCTs of statins have been inconsistent in their demonstration of an association between statin utilization and impaired neurocognitive function 52, 53, 54, 55. PCSK9 inhibitors are not known to inhibit de novo cholesterol synthesis or to cross the blood–brain barrier; nevertheless, imbalances in neurocognitive side effects between PCSK9 inhibitors and control groups were detected in OSLER (Open‐Label Study of Long‐Term Evaluation Against LDL‐C) 1 and 2 (pooled rate: 0.9% versus 0.3%) and in ODYSSEY LONG‐TERM (1.2% versus 0.5%), as well as 2 large meta‐analyses of lipid‐lowering trials 46, 56. However, these findings were limited by heterogeneity of the examined populations, small numbers of events, and differences in the definition and assessment of neurocognitive events.…”
Section: Discussionmentioning
confidence: 99%
“…De novo glial synthesis of cholesterol in the brain is postulated to be important for synapse formation and function; observational studies and RCTs of statins have been inconsistent in their demonstration of an association between statin utilization and impaired neurocognitive function 52, 53, 54, 55. PCSK9 inhibitors are not known to inhibit de novo cholesterol synthesis or to cross the blood–brain barrier; nevertheless, imbalances in neurocognitive side effects between PCSK9 inhibitors and control groups were detected in OSLER (Open‐Label Study of Long‐Term Evaluation Against LDL‐C) 1 and 2 (pooled rate: 0.9% versus 0.3%) and in ODYSSEY LONG‐TERM (1.2% versus 0.5%), as well as 2 large meta‐analyses of lipid‐lowering trials 46, 56. However, these findings were limited by heterogeneity of the examined populations, small numbers of events, and differences in the definition and assessment of neurocognitive events.…”
Section: Discussionmentioning
confidence: 99%
“…Khan et al . 18 also published a meta-analysis evaluating the rates of ischaemic stroke with the use of PCSK9 inhibitors. The authors have divided the studies into two groups, early Phase II–III studies and long-term studies, and concluded that the incidence of ischaemic strokes were similar.…”
Section: Discussionmentioning
confidence: 99%
“…The authors have divided the studies into two groups, early Phase II–III studies and long-term studies, and concluded that the incidence of ischaemic strokes were similar. 18 Both of these investigations also lack the cohorts included in the FOURIER/EBBINGHAUS and GLAGOV trials. 8,15 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations